The Global and Western Indian Ocean Dispersal of House Geckos From Asia Using Historical and Mitochondrial DNA Perspectives - Rocha, Sara; Trinks, Alexandra; Harris, D. James; Larson, Greger; Cheke, Anthony S. (Frontiers in Ecology and Evolution, 2022)
Seven species of house geckos occur across the scattered islands of the Indian Ocean. Two of these, Hemidactylus frenatus and H.parvimaculatus are both widespread and possess distribution profiles that suggest pre-European, or perhaps natural dispersal to some islands. Of these, only H. frenatus currently has sufficient molecular data to begin exploring dispersal patterns. This species is one of the most successful reptile colonists, as demonstrated by its global, pantropical distribution. While in some areas, such as Australia and continental South America, its dispersal patterns are both recent and well-known, early historical records of Hemidactylus in the Indian Ocean islands suggest early and/or potentially non-human-mediated dispersals. Here, we reviewed the historical literature and combined those reports with an assessment of mitochondrial DNA diversity of a global sampling of H. frenatus samples that included modern and museum specimens. Our results corroborate previous studies and demonstrate the relatively high diversity within this species’ native range in Southeast Asia. In addition, the phylogenetic analysis suggests both a potential cryptic species complex, as well as global geographic structuring of different H. frenatus mitochondrial lineages. This has important implications for many comparative studies of this complex. Frequent and ongoing dispersals and colonisations complicate the identification of potentially older migration patterns. Further assessments including additional samples and analyses of additional genetic markers are necessary to disentangle older from more recent dispersals within this intriguing species.